2010
DOI: 10.1016/j.ydbio.2010.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The polarity protein Pard3 is required for centrosome positioning during neurulation

Abstract: SUMMARY Microtubules are essential regulators of cell polarity, architecture and motility. The organization of the microtubule network is context-specific. In non-polarized cells, microtubules are anchored to the centrosome and form radial arrays. In most epithelial cells, microtubules are noncentrosomal, align along the apico-basal axis and the centrosome templates a cilium. It follows that cells undergoing mesenchyme-to-epithelium transitions must reorganize their microtubule network extensively, yet little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 38 publications
6
55
2
Order By: Relevance
“…The centrosome, through its inherent MTorganizing activity and complex protein composition (Bornens, 2002;Doxsey, 2001), as well as its associations with other cellular organelles (Badano et al, 2005), could mediate multiple processes to influence axon formation or neurite identity in multipolar cells. The Golgi apparatus, which is crucial for directional protein transport (Sütterlin and Colanzi, 2010) and is a significant source of MTs in polarized migrating cells (Efimov et al, 2007), has been shown to colocalize with the centrosome (de Anda et al, 2010;de Anda et al, 2005;Hong et al, 2010;Pouthas et al, 2008;Zmuda and Rivas, 1998). Perhaps centrosome positioning at the base of a nascent axon is important not only for creating a polarized MT network, but also for regulating selective transport and trafficking of molecules that define axon identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The centrosome, through its inherent MTorganizing activity and complex protein composition (Bornens, 2002;Doxsey, 2001), as well as its associations with other cellular organelles (Badano et al, 2005), could mediate multiple processes to influence axon formation or neurite identity in multipolar cells. The Golgi apparatus, which is crucial for directional protein transport (Sütterlin and Colanzi, 2010) and is a significant source of MTs in polarized migrating cells (Efimov et al, 2007), has been shown to colocalize with the centrosome (de Anda et al, 2010;de Anda et al, 2005;Hong et al, 2010;Pouthas et al, 2008;Zmuda and Rivas, 1998). Perhaps centrosome positioning at the base of a nascent axon is important not only for creating a polarized MT network, but also for regulating selective transport and trafficking of molecules that define axon identity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that DN-CLIM causes apical mispositioning of the centrosome and reduces its motility. Interestingly, the centrosome not only regulates MT assembly and organization, but its position and motility are also controlled by MT dynamics (de Anda et al, 2010;Hong et al, 2010). LIM-HD activity could potentially regulate any of these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…apicalbasal polarity). In epithelia, centrosomes are typically located near the apical surface (Hay, 2005;Baum et al, 2008;Hong et al, 2010), whereas in migrating mesenchymal cells, centrosomes frequently assume a position between the leading edge and the nucleus. During zebrafish gastrulation, lateral ectoderm and mesoderm cells migrate towards the dorsal midline as a cohesive sheet or as individual cells, respectively (Solnica-Krezel, 2005).…”
Section: Dynamic Centrosome Localization and Behavior During Zebrafismentioning
confidence: 99%
“…Moreover, nucleus-centrosome axes provide information on the organisation of the microtubule network, which is cell type specific (Bacallao et al, 1989;Meads and Schroer, 1995;Müsch, 2004;Brodu et al, 2010;Hong et al, 2010). It is known that microtubules regulate, and are regulated by, points of cell-cell contact (Chausovsky et al, 2000;Waterman-Storer et al, 2000;Yap and Manley, 2001;Ligon and Holzbaur, 2007), raising the possibility that microtubule network organisation is regulated at the supracellular or tissue level, as has recently been shown for the actomyosin system (Martin et al, 2009;Rauzi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%